Perbandingan Efektivitas antara Model Kooperatif Jigsaw dan TGT dalam Meningkatkan Keterampilan Bermain Sepak Bola pada Siswa Sekolah Dasar - Bayu Rizki Alfarizi; Agus Mahendra; Mukhlisin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to compare the effectiveness of the Jigsaw and Teams Games Tournament (TGT) cooperative learning models in improving the soccer playing skills of elementary school students. This study employed a quantitative approach with a quasi-experimental two-group pretest–posttest design. The population of this study consisted of all students of SDN 139 Sukarasa, Bandung City, totaling 274 students, with a sample of 40 fifth-grade students selected using purposive sampling and divided into the Jigsaw and TGT groups. Data were collected using the Game Performance Assessment Instrument (GPAI), which measures the aspects of decision making, skill execution, and support. The data were analyzed using the Shapiro–Wilk normality test, homogeneity test, Wilcoxon Signed Rank Test, and Mann–Whitney U Test. The results showed that both cooperative learning models had a significant effect on improving students’ soccer playing skills. However, the TGT cooperative learning model demonstrated higher effectiveness compared to the Jigsaw model, as indicated by the acceptance of H₁ with a significance value (Sig) < 0.001. Therefore, the implementation of cooperative learning models, particularly TGT, can be an effective alternative to improve elementary school students’ soccer playing skills. Keywords: Jigsaw, Soccer Playing Skills, Cooperative Learning Model, Physical Education, Teams Games Tournament